Evaluation of Perinatal Outcomes in Women with a History of Recurrent Consecutive Spontaneous Abortions: Retrospective Cohort Study - F. Hassan, Mahmoud; Ali, Yahia Z.; Abdallah, Enas A. A.; Moussa, Nehal; Sewidan, Ahmed (Journal of Neonatal Surgery, 2025)
Objective. To assess how recurrent consecutive spontaneous abortion (RCSA) affects the mother and baby in future pregnancies. Materials and Methods. A retrospective cohort study was carried out at Suez Hospital in Egypt. It examined the electronic medical records of pregnant women between the ages of 15 and 49 years who had non-anomalous singleton pregnancies. The study looked at 7,718 women, of whom 172 had a history of recurrent consecutive spontaneous abortion (defined as two or more consecutive pregnancies that ended in abortion). The outcomes for mothers and their newborns were compared for those in the RCSA group versus a control group of women who had ≤ one abortion. A multivariate logistic regression analysis was carried out to adjust for possible confounding variables that could have influenced the study's results. Results. Women with a history of RCSA had significantly higher risks of early-onset-preeclampsia [Adjusted odds ratio (aOR) = 3.13; 95% confidence interval (CI): 1.12–8.72], placenta-previa (aOR = 2.73; 95% CI: 1.09–6.81), placental-abruption (aOR = 3.3; 95% CI: 1.18–9.23), preterm-birth (aOR = 1.79; 95% CI: 1.1–2.91), and small-for-gestational-age infants (aOR = 1.72; 95% CI: 1.03–2.87). These associations remained significant after adjusting for potential confounders. Conclusion. A history of RCSA is linked to an increased risk of adverse obstetric and neonatal outcomes, likely due to underlying placental dysfunction. Therefore, women with a history of RCSA need closer monitoring during subsequent pregnancies to optimize pregnancy outcomes.